The Synoptic Problem in Rabbinic Literature - Cohen, Shaye J.D (Brown Judaic Studies, 2020)
This volume contains six essays that address the ""synoptic problem"" in the study of rabbinic literature. As a whole, they argue for the utility of recognizing that rabbinic documents are as much collections of traditions as they are well-crafted documents only to be considered in and of themselves.